Reversal of Multidrug Resistance by Symmetrical Selenoesters in Colon Adenocarcinoma Cells - Bálint Rácz; Annamária Kincses; Krisztián Laczi; Gábor Rákhely; Enrique Domínguez-Álvarez; Gabriella Spengler (MDPI AG, 2023)
Recently, selenium containing derivatives have attracted more attention in medicinal chemistry. In the present work, the anticancer activity of symmetrical selenoesters was investigated by studying the reversal of efflux pump-related and apoptosis resistance in sensitive and resistant human colon adenocarcinoma cells expressing the ABCB1 protein. The combined effect of the compounds with doxorubicin was demonstrated with a checkerboard assay. The ABCB1 inhibitory and the apoptosis-inducing effects of the derivatives were measured with flow cytometry. Whole transcriptome sequencing was carried out on Illumina platform upon the treatment of resistant cells with the most potent derivatives. One ketone and three methyl ester selenoesters showed synergistic or weak synergistic interaction with doxorubicin, respectively. Ketone selenoesters were the most potent ABCB1 inhibitors and apoptosis inducers. Nitrile selenoesters could induce moderate early and late apoptotic processes that could be explained by their ABCB1 modulating properties. The transcriptome analysis revealed that symmetrical selenoesters may influence the redox state of the cells and interfere with metastasis formation. It can be assumed that these symmetrical selenocompounds possess toxic, DNA-damaging effects due to the presence of two selenium atoms in the molecule, which may be augmented by the presence of symmetrical groups.